Case Control Study of Rotavirus Vaccine Effectiveness in Portugal During 6 Years of Private Market Use. Issue 5 (May 2015) - Marlow, Robin; Ferreira, Muriel; Cordeiro, Eugénio; Trotter, Caroline; Januário, Luis; Finn, Adam; Rodrigues, Fernanda
Abstract : Background: Although recommended by the vaccine committee of the Portuguese Paediatric Society, rotavirus vaccines have not been included in the routine immunization schedule. They have been available privately since 2006 with estimated coverage reaching approximately 30%. However, unlike other European countries using the vaccine, sentinel surveillance has detected fluctuations but no clear trends in the rate of gastrointestinal disease presentations. In this study, we set out to establish the real world effectiveness of rotavirus immunization in this low vaccine coverage setting. Methods: We carried out a test-negative case control study on a population of children attending a regional pediatric hospital, between 2006 and 2012, with symptoms of acute gastroenteritis and producing a stool sample for routine rotavirus testing. We calculated exposure odds ratio (ratio of odds of antecedent vaccination among cases compared with controls) to derive vaccine effectiveness ([1 − adjusted odds ratio]/100) against both hospital attendance and admission. Results: Vaccine effectiveness against attendance with rotavirus acute gastroenteritis was 83.7% (95% confidence interval: 73.9–89.8) and against hospital admission was 96.1% (95% confidence interval: 83.8–99.1). No significant difference between the 2 available vaccines was detected. Conclusion: Both rotavirus vaccines offer a high degree of individual protection in this population.